Avant Garde Alleviation -Cancer Immunotherapy - Bajaj, Anubha (Journal of Clinical and Diagnostic Pathology, 2019)
Novel cancer therapeutics are superior and  prevalent in the current scenario although a subset may not be satisfactorily alleviated or undergo disease relapse with the adoption of conventional chemotherapeutic agents.  Cancer cells can comfortably elude immune destruction as  interaction of cancer cells  with native  immune cells within  tissue microenvironment is a cogent factor in evasion of cancer cells  from pertinent immune surveillance. Thus, cancer immunotherapy can be safely contemplated as  an efficacious and contemporary  treatment modality  for managing  various malignant disorders.
Keywords: Immune; cancer; tissue; cells